How Long Does It Take to Stop? Are Children Able to Stop on Demand? - Ernst Tomasch; Heinz Hoschopf; Bernd Schneider; Bettina Schützhofer; Martin Söllner; Barbara Krammer-Kritzer; Michael Plank; Hannes Glaser (Applied Sciences)
Children’s physical and cognitive development plays a crucial role in their ability to react appropriately in dynamic traffic situations. One key aspect of traffic safety is the ability to stop movement quickly and accurately after receiving a stop signal. Distraction is a major contributor to road accidents, especially among children who are easily distracted and may not be fully aware of the traffic situation. It is crucial to understand that children up to a certain age may struggle to halt their movement once initiated. This study indicates that the stopping distance, time, and deceleration of children aged six to ten years after a specific stop signal at different speeds are strongly influenced by the speed of movement and the age of the children. The results show that in the “walking” test configuration, the children were able to stop within a range of 0.47 m to 0.63 m, with a shorter distance for older children. The stopping time ranges from 0.84 s to 1.21 s and correlates positively with age. The stopping time and distance of children were measured in both “running” and “walking” test configurations across different age groups. However, in the “running” test configuration, stopping distance is almost the same across all age groups, with children requiring between 1.72 m and 1.84 m and a stopping time ranging from 1.17 s to 1.28 s. In the “walking” test configuration, children are able to decelerate between 0.91 m/s2 and 1.57 m/s2, while in the “running” test configuration, they are able to decelerate between 2.24 m/s2 and 3.19 m/s2.